2020
DOI: 10.1097/md.0000000000019248
|View full text |Cite
|
Sign up to set email alerts
|

Total bile acid-to-cholesterol ratio as a novel noninvasive marker for significant liver fibrosis and cirrhosis in patients with non-cholestatic chronic hepatitis B virus infection

Abstract: Although serum bile acids and total cholesterol (TC) are closely related to liver cirrhosis, the potential diagnostic value of total bile acid-to-cholesterol ratio (TBA/TC) for liver fibrosis is unclear. The present study aimed to evaluate the value of TBA/TC in the diagnosis of cirrhosis and the relationship between TBA/TC and significant liver fibrosis in chronic hepatitis B virus (HBV) infected patients without cholestasis. 667 patients with alkaline phosphatase (ALP) ≤ 1.5 upper limit of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…GO:0051264 is connected with mono-olein metabolism. Serum bile acids and total cholesterol (TC) are closely related to liver cirrhosis; the potential diagnostic value of total bile acid-to-cholesterol ratio (TBA/TC) for liver fibrosis has been proven ( Yan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…GO:0051264 is connected with mono-olein metabolism. Serum bile acids and total cholesterol (TC) are closely related to liver cirrhosis; the potential diagnostic value of total bile acid-to-cholesterol ratio (TBA/TC) for liver fibrosis has been proven ( Yan et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated plasma bile acids, in particular, both free and conjugated CDCA, have been reported to be elevated in cirrhotic patients relative to healthy volunteers 22 . Total bile acids and total bile acids/cholesterol ratio were found to be elevated in 451 cirrhotic patients compared with 216 non-cirrhotic patients with non-cholestatic chronic HBV infection in China 23 . An investigation of 32 cirrhotic patients and 27 healthy volunteers examined 12 serum bile acids using UPLC-TQMS and reported that serum concentrations of the conjugated primary bile acids, taurocholic acid (TCA), glycocholic acid (GCA) and taurochenodeoxycholic acid (TCDCA) were positively associated with Child–Pugh classification 24 .…”
Section: Discussionmentioning
confidence: 95%
“…Serum TBAs are also significantly increased in cirrhosis due to hepatitis B virus (HBV) and hepatitis C virus (HCV) infection 42,43 . Yan et al demonstrated an association of cirrhosis and serum TBAs to total cholesterol ratio in non-cholestatic chronic HBV infection 44 . Serum TBAs, particularly conjugated BAs, are elevated in HBV cirrhosis with a progressive increase as CTP grade advances 45 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%